Saphenous Vein Vasa Vasorum as a Potential Target for Perivascular Fat-Derived Factors - Loesch,Andrzej (2020)
Abstract Perivascular adipose tissue (PVAT) is a source of factors affecting vasomotor tone with the potential to play a role in the performance of saphenous vein (SV) bypass grafts. As these factors have been described as having constrictor or relaxant effects, they may be considered either beneficial or detrimental. The close proximity of PVAT to the adventitia provides an environment whereby adipose tissue-derived factors may affect the vasa vasorum, a microvascular network providing the vessel wall with oxygen and nutrients. Since medial ischaemia promotes aspects of graft occlusion the involvement of the PVAT/vasa vasorum axis in vein graft patency should be considered.